ESTIMATING MARKET POWER OF RICE EXPORTERS TO IRAQ DURING THE PERIOD (2005-2021) - Amna Aqeel Majeed; Awf A. Alsaad, Awf A. Alsaad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study aimed to determine and analyze market power among rice exporters to the Iraqi market by estimating the residual demand for different types of rice. Four countries were included in the study: Thailand, India, Pakistan, and the United States of America. The inverse residual demand elasticity of these countries was measured during the study period, 2005-2021. The results showed market power among the countries supplying rice to the Iraqi market. Thailand has greater market power than the United States due to lower export prices and a weaker local currency. On the other hand, competition between Pakistan and India was intense in the Iraqi rice market. The study recommended government intervention to support farmers in improving productivity, enhancing food security, and reducing dependence on imports.